Pendidikan dan Kompensasi di Era Teknologi: Faktor Utama dalam Meningkatkan Motivasi Kerja Karyawan - Pindasari, Nanang (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This study aims to examine the influence of education and compensation on employee work motivation at Suzuki Dealer PT. Megah Putera Kendari. Rapid technological advancements pose new challenges, including the demand for adaptation to big data and automation, which require employees with relevant educational skills. This research uses a quantitative approach with a sample of 55 employees, selected through proportional stratified random sampling. Data analysis was conducted using multiple linear regression with SPSS 23 software, including normality tests, t-tests, F-tests, and the coefficient of determination (R²). The results show that education has a positive and significant effect on work motivation. Good educational qualifications contribute to increasing employee motivation. Additionally, compensation also has a positive and significant effect on work motivation. The better the compensation provided, in line with the principles of fairness, appropriateness, and equity, the higher the employee work motivation. This study highlights the importance of education and fair compensation in enhancing work motivation at PT. Megah Putera Kendari.